Perancangan Sistem Informasi Produk Menggunakan CMS Wordpress di PT. Global Medika Indoselaras - Aditya Ramadhan; Fajar Satriadi; Rahul Diaz Gaharu; Khanif Faozi (OKTAL : Jurnal Ilmu Komputer dan Sains, 2025)
AThe advancement of information technology encourages companies to manage product information more effectively and efficientyly. PT. Global Medika Indoselaras, a company engaged in the distribution of medical devices, requires a product information system that is easy to manage and accessible. This study aims to design a product information system using the WordPress Content Management System (CMS). The methodology includes requirement analysis, system design, implementation, and testing phases. The results show that the developed system can display product information in a structured manner, simplify the data updating process, and improve information accessibility for both internal and external users. By utilizing WordPress, the company can manage content independently without relying on developers, thereby enhancing work efficiency. This system is expected to serve as an informative medium that’s supports business processes and customer service.